Peran Motivasi dalam Meningkatkan Kualitas Pembelajaran Siswa di Sekolah - Habsy, Bakhrudin All; Shafira, Rizka Rusydah Reza; Rahmawati, Maria Yustiana; Habibah, Noviana (TSAQOFAH, 2024)
The quality of education that students receive at school is important in shaping their future. One of the main factors that influences the quality of learning is motivation. This article discusses in depth the critical role of motivation in improving the quality of student learning in schools. We explain various aspects of motivation, including intrinsic and extrinsic motivation, and how motivation influences students' learning behavior. We also present theories of motivation in learning. Understanding the role of motivation in improving the quality of student learning is an important step in the quest for a more meaningful and productive education. In this research, researchers used qualitative literature study methods.